Study of Energy Parameters of Some Er(III) Doped Systems - Verma, R.S.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
An electronic spectral investigation of ten Er(lIl) doped systems has been attempted to evaluate electronic spectral parameters, viz., Slater-Condon (Fk), Racah (Ek), Lande (ζ4f) and nephelauxetic ratio (β) in order to examine variation in these electronic spectral parameters as a result of change in ligand.